Active shedding of Neospora caninum detected in Australian wild canids in a nonexperimental context. Issue 4 (7th June 2021) - Davidson, Mikaeylah J.; Huaman, Jose L.; Pacioni, Carlo; Stephens, Danielle; Hitchen, Yvette; Carvalho, Teresa G.
Abstract: Infection with Neospora caninum parasites is a leading cause of reproduction losses in cattle worldwide. In Australia, this loss is estimated to total AU$110 million every year. However, despite this considerable economic impact, the transmission cycle and the host(s) responsible for the sylvatic transmission of the parasite remain to be defined. Dingoes ( Canis familiaris ) have been suggested to be a wildlife host of N. caninum in Australia, but this is yet to be proven in a nonexperimental setting. This study aimed to determine the prevalence of natural N. caninum shedding in Australian wild dogs (defined as dingoes, dingo‐domestic dog hybrids and feral dogs) by performing molecular analysis of faecal samples collected in wild dog populations in south‐east Australia. Molecular analysis allowed host species identification and dingo purity testing, while genetic analysis of Coccidia and Neospora conserved genes allowed for parasite identification. Among the 115 samples collected and determined to belong to dingoes, dingo‐domestic dog hybrids and foxes, Coccidian parasites were detected in 41 samples and N. caninum was identified in one sample of canine origin from South East Australia (Mansfield). Across all samples collected in Mansfield only 15 individuals were successfully identified by genotype. Thereby our study determined that 6.7% (1/15, 95% confidence intervals 1.2–29.9) of wild dogs were actively shedding N. caninum oocysts at this site. Further, only four individuals were identified at a second site (Swift Creek), and none were positive. This study conclusively confirms the role of wild dogs in the horizontal transmission of N. caninum parasites in Australia.